IgG4-related disease presenting with combined pulmonary fibrosis and emphysema (CPFE). (2018) - Kono, Masato; Nakamura, Yutaro; Oyama, Yoshiyuki; Saito, Go; Koyanagi, Yu; Miyashita, Koichi; Tsutsumi, Akari; Enomoto, Yasunori; Kobayashi, Takeshi; Miki, Yoshihiro; Hashimoto, Dai; Enomoto, Noriyuki; et al.
Abstract: A 64-year-old man was admitted to our hospital with an abnormal chest shadow. The patient was a current-smoker and had a past illness of autoimmune pancreatitis with a high serum level of IgG4, 348 mg/dL. Chest CT showed upper-lobe emphysema, and lower-lobe reticulation with honeycombing, suggestive of combined pulmonary fibrosis with emphysema (CPFE). Surgical lung biopsy was revealed a usual interstitial pneumonia pattern with marked infiltration of IgG4-positive plasma cells. The patient was diagnosed with IgG4 related disease (IgG4-RD) presenting with CPFE. Pulmonary manifestation was improved by corticosteroid therapy. IgG4-RD may be an underlying condition in patient with CPFE.